The influence of the guest cavitation loading degree in fractal nanohybrids GaSe〈β-cyclodextrin〈FeSO₄〉〉 on the current passing and polarization processes. The giant “battery spin” effect at room temperature - Ivashchyshyn, F.O.; Grygorchak, I.I.; Hryhorchak, O.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2017)
The investigation results of clathrate properties GaSe〈β-cyclodextrin〈FeSO₄〉〉 of the hierarchical architecture with the fourfold expansion at different degrees of a guest cavitation loading have been presented. Based on the frequency dependence of the specific complex impedance, the changes of the impurity energy spectrum expanded matrix parameters as a result of forming the supramolecular ensembles on its basis are clarified. For some architectures, impedance, photo, and magneto responses showed the extraordinary behavior of the magnetoimpedance and photoconductivity, and also the giant negative photodielectric and the colossal magnetocapacitance effects at room temperature, which open new possibilities for their practical application.